IDENTIFIKASI DAMPAK PERUBAHAN IKLIM TERHADAP SEKTOR INDUSTRI MINYAK DAN GAS - Abdullah Rizky Agusman; Eko Prastio; Arief Nur Hidayat (Jurnal Bhara Petro Energi, 2026)
Climate change is an unavoidable issue for the future. Increasing greenhouse gas (GHG) emissions are causing climate change, which is already being felt in various parts of the world. The oil and gas industry is one of the sectors most vulnerable to the impacts of climate change. The entire oil and gas value chain, from production and transportation to refining, is affected differently by the impacts of climate change. Mitigation and adaptation measures are needed to prevent significant financial losses.